Electronic Based Practicum Guide Using Inquiry Models to Improve Science Process Skills and Student Learning Outcomes - Utari Prisma Dewi; Syafriani (Jurnal Penelitian Pendidikan IPA, 2024)
Low science process skills also result in low learning outcomes. So the solution is to develop an electronic-based practicum guide using an inquiry model on measurement material. This research aims to develop an electronic-based practicum guide using an inquiry model on measurement material to improve science process skills and student learning outcomes. The development model is the ADDIE model. The research instruments used were expert and practitioner validation questionnaires, student response assessment questionnaires and pretest-posttest results. Data was analyzed quantitatively descriptively. The results of the N-gain test are 16 students who got a score of (g) ≥ 0.7, 14 students who got a score of (g) ≥ 0.3, and 14 students who got a score of (g) <0.3 as many as 0 people. Based on the results of this research, it can be concluded that electronic-based practicum guides using inquiry models in measurement material can improve science process skills and student learning outcomes.